Biochemical characterization of two xylanases from yeast Pseudozyma hubeiensis producing only xylooligosaccharides - Adsul, Mukund G.; Bastawade, Kulbhushan B.; Gokhale, Digambar V. (Bioresource Technology, 2009)
Two distinct xylanases from Pseudozyma hubeiensis NCIM 3574 were purified to homogeneity. The molecular masses of two native xylanases were 33.3 kDa (PhX33) and 20.1 kDa (PhX20). PhX33 is predominant with alpha-helix and PhX20 contained predominantly beta-sheets. Xylanase, PhX33, possesses three tryptophan and one carboxyl residues at the active site. The active site of PhX20 comprises one residue each of tryptophan, carboxyl and histidine. Carboxyl residue is mainly involved in catalysis and tryptophane residues are solely involved in substrate binding. Histidine residue present at the active site of PhX20 appeared to have a role in substrate binding. Both the xylanases produced only xylooligosaccharides (XOS) with degree of polymerization (DP) 3-7 without formation of xylose and xylobiose. These XOS could be used in functional foods or as prebiotics. Lc ms-ms ion search of cryptic digestion of these xylanases revealed that there is no significant homology of peptides with known fungal xylanase sequences which indicate that these xylanases appear to be new. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Cellulase-free xylanase; Pseudozyma hubeiensis; Xylooligosaccharides